2000
DOI: 10.1016/s0167-2789(99)00225-0
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic analysis of subcritical Hopf–homoclinic bifurcation

Abstract: This paper discusses the mathematical analysis of a codimension two bifurcation determined by the coincidence of a subcritical Hopf bifurcation with a homoclinic orbit of the Hopf equilibrium. Our work is motivated by our previous analysis of a Hodgkin-Huxley neuron model which possesses a subcritical Hopf bifurcation [5]. In this model, the Hopf bifurcation has the additional feature that trajectories beginning near the unstable manifold of the equilibrium point return to pass through a small neighborhood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 8 publications
(14 reference statements)
5
57
0
Order By: Relevance
“…also section 1. Other mechanisms that do not explicitly involve canards have been proposed to explain MMOs; examples include break-up of an invariant torus [21], loss of stability of a Shilnikov orbit [16], slow passage through Hopf bifurcation [22], and subcritical Hopf-homoclinic bifurcation [12,13]. While these other mechanisms are consistent with some of the characteristic features of MMOs, they cannot typically explain all of them; see [2].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…also section 1. Other mechanisms that do not explicitly involve canards have been proposed to explain MMOs; examples include break-up of an invariant torus [21], loss of stability of a Shilnikov orbit [16], slow passage through Hopf bifurcation [22], and subcritical Hopf-homoclinic bifurcation [12,13]. While these other mechanisms are consistent with some of the characteristic features of MMOs, they cannot typically explain all of them; see [2].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Note that since the Hopf bifurcations are subcritical the unstable periodic orbits created at the bifurcation are not involved in this behavior, cf. [20].…”
Section: Discussionmentioning
confidence: 99%
“…Guckenheimer and Willms [95] observed that a subcritical (ordinary) Hopf bifurcation may result in large regions of the parameter space being funneled into a small neighborhood of a saddle equilibrium with unstable complex eigenvalues. After trajectories come close to the equilibrium, SAOs grow in magnitude as the trajectory spirals away from the equilibrium.…”
Section: Mmos Due To a Singular Hopf Bifurcationmentioning
confidence: 99%
“…In this case, the returns are likely to come close enough to q that they will give rise to long epochs of small, slowly growing oscillations. See Guckenheimer and Willms [95] for a three-dimensional example and Guckenheimer et al [89] for a high-dimensional example occurring in a neural model. We remark that, although this mechanism for creating MMOs applies to a single-time system, the Hopf bifurcation naturally introduces a slow time scale in the system associated with the real parts of the unstable complex eigenvalues.…”
Section: Other Mmo Mechanisms In Odesmentioning
confidence: 99%